Conservative, Surgical, and Prosthetic Treatment of a Patient with a Periapical Lesion Associated with an Atypical Intraoral Sinus Tract - Michael Wolgin; Peter Tschoppe; Andrej M. Kielbassa (Case Reports in Dentistry)
This report describes a clinical case with an atypical intraoral sinus tract formation from diagnosis and treatment to short-term outcome and definitive prosthetic rehabilitation. In detail, the patient underwent conservative nonsurgical root canal treatment followed by guided bone augmentation of the regions involved in periapical inflammation and sinus tract formation. The removal of the inflammatory source of the lesion as well as the affected tissue clearly led to a healing of the surrounding bone tissues. Subsequently, the tooth was reconstructed using a fibreglass post and a metal-ceramic crown; an implant was successfully placed in the previously inflamed bone region.